Pengaruh Pengenalan Lapangan Persekolahan (PLP) dan Keaktifan Berorganisasi terhadap Kesiapan Menjadi Guru - Faiz Fauzan; Khresna Bayu Sangka; Leny Noviani (Journal on Education, 2024)
This research aims to knowing the effect of introduction to the school field on the readiness to become teachers and knowing the influence of organizational activity on the readiness to become teachers of UNS Economics Education Students. This research uses quantitative research methods with a population of 170 students and a sample of 120 students consisting of active Economic Education students from the class of 2019 and 2020. The sampling technique used was probability sampling with a proportional random sampling sub-technique. The validity and reliability testing techniques used in this research are Korelasi Product Moment and Cronbach’s Alpha. The data collection method used was a questionnaire distributed online. Data analysis in this study used Multiple Linear Regression which was calculated with the help of SPSS version 25 software. The results of the study showed that (1) there was a positive influence between introduction to the school field on readiness to become a teacher, (2) there was a positive influence between organizational activity on readiness to become a teacher.